KRISIS KEUANGAN EUROZONE: Studi Ekonomi dan Perbankan Islam - Muhammad Zulhilmi (Sharia and Law Faculty, 2017)
Crisis arising from the lack of liquidity with asset bubbles, causing the government borrow loans to develop the concept of welfare state that once popularized in the eurozone. As a result, the loan continues to increase without any real investment coupled macroeconomics. In Islamic financial institutions, transparency and accountability of financial institutions strengthen the international financial system, because the assets contributed to the country’s financial stability. Banking institutions continue to be supervised and even cooperate with initiatives to strengthen stability by building cooperation supervision such as: the Accounting and Auditing Organization for Islamic Financial Institute, the Islamic Financial Services Organization, the International Islamic Financial Market and Islamic Rating Agency. These institutions will strengthen the international Islamic financial architecture and promote the stability of the larger Islamic finance.